2019
DOI: 10.3390/su11143846
|View full text |Cite
|
Sign up to set email alerts
|

Review of Methodological Choices in LCA-Based Textile and Apparel Rating Tools: Key Issues and Recommendations Relating to Assessment of Fabrics Made From Natural Fibre Types

Abstract: Life cycle assessment (LCA) is a key tool for determining environmental impacts for textiles and apparel and is the basis for the publicly available Higg Material Sustainability Index (MSI) developed by the Sustainable Apparel Coalition (SAC). This paper reviews and evaluates the Higg MSI with respect to rating of fabrics made from natural fibre types, with the aim of providing a constructive analysis of methodological issues identified by comparison with the International Standards and LCA guidelines. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…ReCiPe Hierarchist normalisation methods are based on a study by [75], utilizing the population of EU25+3 of 450 million citizens [76], in which normalised results are expressed as person equivalents, or the annual impact of an average European person in the year 2000 [68,76]. To determine relevant impact categories, LCAs on garments [29,33,60,62,70,77] were reviewed to understand the important impacts from an industry and research perspective that should be considered. This was taken into account in concurrence with the significant impact categories from the results.…”
Section: Life-cycle Impact Assessment (Lcia)mentioning
confidence: 99%
See 1 more Smart Citation
“…ReCiPe Hierarchist normalisation methods are based on a study by [75], utilizing the population of EU25+3 of 450 million citizens [76], in which normalised results are expressed as person equivalents, or the annual impact of an average European person in the year 2000 [68,76]. To determine relevant impact categories, LCAs on garments [29,33,60,62,70,77] were reviewed to understand the important impacts from an industry and research perspective that should be considered. This was taken into account in concurrence with the significant impact categories from the results.…”
Section: Life-cycle Impact Assessment (Lcia)mentioning
confidence: 99%
“…For example, the company Reformation uses RefScale, an LCA tool to calculate the CO2, water use, and waste footprints of their garments [78]. The Higg Material Sustainability Index (Higg MSI), created by the Sustainable Apparel Coalition and used commonly in the apparel industry assesses four impact categories: global warming, eutrophication, water scarcity, and abiotic resource depletion/fossil fuels [77]. This study analysed the commonly reported impact category of GWP, which showed positive results for the rental scenarios.…”
Section: Choice and Relevance Of Lca Impact Categoriesmentioning
confidence: 99%
“…A review of the Higg MSI against international LCA standards and guidelines found that there are a number of inconsistencies and improvements that could be implemented to ensure it provides robust, accurate and trustworthy results. This review concluded that in its current form the Higg MSI had limited capability to help stakeholders compare fabric types in order to select those with lower environmental impacts (Watson and Wiedemann 2019).…”
Section: Lca-based Toolsmentioning
confidence: 99%
“…Raw cotton is the first stage of the global cotton value chain, which includes the following phases: growing cotton, ginning (separating the cotton fibre from the seed and cleaning it), blending cotton from different regions or with manmade fibres (MMF) and spinning into yarn, textile manufacturing, garment manufacturing and retailing [3]. Environmental impacts and social aspects of a product's lifecycle can be assessed through the Lifecycle Assessment (LCA) and Social Lifecycle Assessment (S-LCA), such as energy and water use, number of jobs created, and the positive and negative impact on consumers, local community, society and value chain actors [4][5][6]. Taking a lifecycle perspective, the post-purchase stages of consumer use, reuse or recycling and eventual disposal further add to the high environmental and social impact of the apparel industry [7].…”
Section: Introductionmentioning
confidence: 99%